The future of criminology - Loeber, Rolf.; Welsh, Brandon, 1969- (New York ; Oxford : Oxford University Press, 2012)
This title takes stock of the major advances and developments that have taken place in the past several decades and asks where the field of criminology is headed. In 33 brief essays, the field's leading scholars provide their views into the future of what needs to be done in research, policy, and practice in the discipline.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminology; Crime prevention